Caregiver Support as a Predictor of Self-Care in Older Adult with Hypertension: A Cross-Sectional Analysis from West Sumatera Nursing Home - Jepisa, Tomi; Syarli, Setiadi; Husni; Ahmaniyah (RRZ Scientific Publishing, 2025)
Hypertension is a prevalent non-communicable disease in older adults that significantly affects functional abilities and quality of life. Half of the older adults had hypertension in nursing homes in West Sumatera. Caregiver support plays a crucial role as an external factor that can strengthen the motivation and ability of older adults to manage their health conditions independently. Most studies have focused on home-based care or informal caregivers. Therefore, this study aimed to assess the relationship between caregivers’ social support and self-care behavior in older adults with hypertension in nursing homes. This cross-sectional study, conducted from April to August 2025 at Sabai Nan Aluih Sicincin Nursing Home in West Sumatera, included 86 older adults with hypertension (aged ≥60 years) using total sampling. Data were collected via the 20-item Caregiver Social Support Questionnaire and the 25-item Hypertension Blood Pressure Self-Care Profile (HBP-SCP), both culturally adapted and reliable. Data were analyzed using descriptive analysis and chi-square tests. Result: Participants (mean age 72.4 years) were mostly female (61.6%) and widowed (74.4%). High caregiver support was perceived by 53.5% of the participants. Good self-care was demonstrated by 43.0% of participants, with the highest adherence in medication use and the lowest in blood pressure monitoring and physical activity. A significant association was found between caregiver support and self-care behavior (p=0.005). Conclusion: This study confirmed a significant positive association between caregiver support and self-care in older adults with hypertension in West Sumatra nursing homes. This underscores the critical role of formal caregivers in institutional settings. The findings highlight the need for comprehensive caregiver training in technical skills, communication, and motivational strategies. Future longitudinal research is recommended to explore causality and develop targeted interventions. Fostering robust caregiver support is essential for promoting independence and improving the quality of life of these individuals.